2022
DOI: 10.3389/fphar.2021.724192
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HSP90 Inhibits Proliferation and Induces Apoptosis Through AKT1/ERK Pathway in Lung Cancer

Abstract: Lung cancer is one of the most common malignant cancers worldwide. Searching for specific cancer targets and developing efficient therapies with lower toxicity is urgently needed. HPS90 is a key chaperon protein that has multiple client proteins involved in the development of cancer. In this study, we investigated the transcriptional levels of HSP90 isoforms in cancerous and normal tissues of lung cancer patients in multiple datasets. The higher expression of HSP90AA1 in cancer tissues correlated with poorer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Studies found that 25% of patients with neuroblastoma showed an MYCN amplification and predicted poor prognosis independently of other factors ( Brodeur et al, 1984 ; Seeger et al, 1985 ). HSP90AA1 , one of the HSP90 isoforms, showed a significant correlation with survival time in lung cancer patients by inhibiting the AKT1 and ERK pathways ( Niu et al, 2021 ) and was upregulated in colorectal cancer ( Szczuka et al, 2021 ). HSP90 regulates the stability of MLKL and RIP3 and is required for TNF-stimulated necrosome assembly ( Zhao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that 25% of patients with neuroblastoma showed an MYCN amplification and predicted poor prognosis independently of other factors ( Brodeur et al, 1984 ; Seeger et al, 1985 ). HSP90AA1 , one of the HSP90 isoforms, showed a significant correlation with survival time in lung cancer patients by inhibiting the AKT1 and ERK pathways ( Niu et al, 2021 ) and was upregulated in colorectal cancer ( Szczuka et al, 2021 ). HSP90 regulates the stability of MLKL and RIP3 and is required for TNF-stimulated necrosome assembly ( Zhao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The serine/threonine kinase AKT (also known as PKB) controls key cellular processes such as proliferation and antiapoptotic effects. Inhibition of HSP90 downregulates the expression of Akt kinase and, as a result, sensitizes tumor cells to proapoptotic factors [ 31 , 32 ]. Focal adhesion kinase (FAK) and integrin-linked kinase (ILK) are critical promoters to cell adhesion.…”
Section: Roles Of Hsp90 In Cancermentioning
confidence: 99%
“…Compared with normal tissue, cancer cell shows a higher expression of HSP90 on mRNA and protein level [ 49 ]. It was reported that the concentration of HSP90 in plasma is associated with the malignant degree of the tumor, which is supported by the clinical data of more than 4000 patients with breast cancer [ 50 ].…”
Section: Hsp90mentioning
confidence: 99%
“…Some clients may mutate or overexpress in pathological cells, which is alleviated by HSP90 inhibitors, indicating a therapeutic role in cancer. The cancer-related clients, including mitogen-activated protein kinase (MAPK) kinase, extracellular signal-regulated kinase (Erk) 1/2, and Akt [ 49 , 51 ], take part in the proliferation, invasion and resistance of cancer cells [ 49 , 52 , 53 ]. For example, A synthetic inhibitor PF-4942847 exerts intensive effects on the viability of cancer cells by inducing apoptosis, delaying OS tumor growth and reducing lung metastasis [ 54 ].…”
Section: Hsp90mentioning
confidence: 99%
See 1 more Smart Citation